El rol de la familia en la inclusión educativa de los estudiantes del sexto año de Educación General Básica. - Alvarado Barzallo, Saddy Maricel (2020)
The present study was developed under the general theme: the role of the family in the inclusive education of sixth-year students of basic general education. Its objective was to analyze the incidence of the role of the family in the educational inclusion of students in the sixth year of basic general education of the Educational Unit "Pedro Franco Dávila" and it was observed that the study population at sometimes did not have the motivation and necessary support that the family must provide in pedagogical settings. It should be noted that children of educational inclusion need that the communication of the educational and family context needs to be optimized so that the guidelines given by the teacher in the educational task are met. As a result, information on the study variables was systematized and the problem was addressed through the application of instruments such as scientific observation, surveys and interviews………..